Axial behaviour of CFST stub columns strengthened with steel tube and sandwiched concrete jackets. (October 2020) - Liang, Hongjun; Li, Weijie; Huang, Yue; Lu, Yiyan
Abstract: This study addresses some key concerns on using steel tube and sandwiched concrete jackets to strengthen intact concrete-filled steel tubular (CFST) columns. The research background lies in engineering cases, in which the functional purpose changes when the structure remains intact. Within the parameters investigated, the load-bearing capacity of columns was enhanced by 114%–199% after being jacketed with steel tube and sandwiched concrete. The observable enhancement depended on section enlargement and the confinement effects of the outer steel tube, the latter of which could account for as large as 19% of the nominal load-bearing capacity. A finite element (FE) model was developed and verified, and the load distribution on components of the strengthened columns was presented. The radial stress between the inner concrete and inner steel tube was validated to increase substantially after the CFST column is jacketed with steel tube and sandwiched concrete. The decrease in the diameter-to-thickness ratio of the outer steel tube contributes to the synchronisation of the inner and sandwiched concrete in reaching peak load and benefits the load increase. A parametric study based on the FE model was conducted, and the effects of estimation error with respect to the properties of existing CFST columns were evaluated. A reasonable match between the outer steel tube grade and sandwiched concrete class was advised. Highlights: The bearing capacity of CFST columns was enhanced by 114%–199% after strengthening. The confinement effects of the outer steel tube could account for as large as 19% of the nominal load-bearing capacity. Load distribution on components was studied using a verified FE model. Interaction between components and confinement effects were investigated numerically.